Innovating Development of the NBAGraduate Attributes - Waychal, Pradeep (Journal of Engineering Education Transformations, 2017)
The main issue the Indian engineering education system has been facing is poor employability. Earlier solutions to tackle the issue were unclear and now the NBA (National Board of Accreditation) has provided solution by identifying a list of graduate attributes.The attribute list has defined what is to be done and has left the task of how it is to be done to the engineering institutes.The colleges are not able to manage the 'how' part due to the heavy curricular load and the paucity of qualified faculty.We present a solution of conducting a one-day workshop on 'innovating success' that can help develop the attributes and identify appropriate final year projects, which can further accentuate the development. We conducted the workshop at a leading college in the state of Maharashtra that was successful in providing opportunities to develop the attributes as per the participants' rating. The workshop also provided a superior learning experience as per the overall workshop rating given by the participants. It was 4.5 out of 5. We need to extend the workshop to two days, or carry out iteration, or design a semester long course to strengthen the development. Given the size of the Indian engineering education system, we would require effective scaling solutions.